Pelatihan desain grafis dan seminar kewirausahaan bagi UMKM sebagai upaya peningkatan kualitas promosi dan pemasaran produk pada masa covid-19 - Wahyuningtias, Fahmawati; Agustina, Rina; Ramadani, Dyah Nisvi; Palupi, Jenny Intan; Adhriani, Sofia; Hidayati, Riska; Nizah, Binta Luthfiana (Nur Science Institute, 2023)
The COVID-19 pandemic has hurt the economy in Indonesia, one of which is the impact on MSMEs. The impact of this pandemic requires MSME players to develop marketing strategies and creativity. MSME players must be more creative and innovative in developing marketing strategies. Therefore, KKN IAIN Salatiga 2022 is carrying out graphic design training and entrepreneurship seminars for MSME players with the aim of MSME players having the skills to create attractive and creative promotions in various e-commerce so that MSME products can be promoted with a broader reach and can attract buyers. The methods used are counseling, graphic design training, and holding entrepreneurship seminars, which are carried out in several stages: preparation, implementation, and evaluation. The results of this Community Service Activity are (1) MSMEs can master material regarding the importance of graphic design, (2) MSMEs are starting to create their product catalogs, and (3) MSMEs are innovating with their brands and product packaging.